Simulating the Aerodynamics Profiles of NACA 4312 Airfoil in Various Incoming Airspeed and Gurney Flap Angle - Sumaryada, Tony; Jaya, Achmad Muharam; Kartono, Agus (Omega: Jurnal Fisika dan Pendidikan Fisika, 2018)
Simulations of the aerodynamics performance of NACA 4312 airfoil at various gurney flap angles and incoming airspeed (wind velocities) have been conducted. The gurney flaps size was set at 5.0% length of the chord line. Two airfoil models with gurney flap at 45° and 90° were simulated and compared with the results of plain airfoil (without gurney flap) model with the incoming airspeed of 10.0 m/s, 70.0 m/s and 200.0 m/s. The results have shown that increasing the value of gurney flap angle to 45° and 90° will increase the lifting force of the airfoil and decrease the drag force.